Dari Pengetahuan ke Tanggung Jawab: Penguatan Kognitif dan Etika Artificial Intelligence Mahasiswa melalui Pembelajaran Berbasis Proyek Kolaboratif - M. Miftach Fakhri; Furqan Ali Yusuf; Dewi Fatmarani Surianto; Ahnaf Riyandirga Ariyansyah Putra Helmy; Della Fadhilatunisa (Vokatek: Jurnal Pengabdian Masyarakat, 2024)
The low cognitive skills and ethical understanding of students in utilizing AI technology are major challenges in higher education in the digital era. This community service aims to improve these aspects through a Participatory Action Research (PAR) approach based on collaborative project-based learning. The method consists of four stages: building collaborative relationships between students, lecturers, and the campus community; implementing real-case-based projects supported by intensive training on AI, ethics, and the preparation of Student Creativity Program Proposals (PKM); reflective analysis of student ideas; and proposal presentations for evaluation. The results show significant improvements in pre-test and post-test scores, both in cognitive aspects (15.52 to 20.52) and ethical understanding (15.52 to 19.31). The implication of this service is that collaborative project-based learning effectively builds students' cognitive and ethical competencies holistically and can be adopted as a learning model to prepare students for responsibly facing technological challenges.